Legal Protection as a Natural Tourism Attraction for Pede Beach Tourists - Indra Ratna Sari; Andin Rusmini (Cigarskruie: Journal of Educational and Islamic Research, 2023)
Legal protection refers to various legal efforts that must be provided by legal officials in order to provide a sense of security, both psychologically and physically from disturbances and various other threats. every organization provided considering the many tourists who experience theft, fraud, and other forms of criminal acts that threaten the safety of tourists. This research aims to see the extent of the government's efforts to protect tourists. The research method used is normative legal research, using a statutory approach. The data analysis method is in the form of normative analytics and literature. In the provisions of article 20 of the Tourism Law mentioned above, tourists have the right to obtain legal protection and security, protection of personal rights for tourism activities that have a major impact. What is regulated in the Tourism Law is the right of tourists, on the other hand it is an obligation of tourism entrepreneurs.